Careers in the computer industry - Greene, Laura. 4 0 16; 5 (New York : Watts, 1983)
Discusses various ways of working with computers for a living, including engineering and technical careers, systems analysis and programming, data processing, computer service jobs, and business uses of computers.
Includes index.
Booklist;Reference and Research Book News
8.2;5-8;5-8
Keywords: 2 -- 0; 6; Vocational guidance;Vocational guidance;Vocational guidance.;Vocational guidance.;Vocational guidance. -- Electronic data processing;Electronic digital computers;Data processing;Computers;Vocational guidance.;Computers;Electronic data processing. -- Juvenile literature.;Juvenile literature; 20; 2